The influence of sustainable sport nutrition practices on youth sports participants - Deng, Jianfeng (Frontiers in Nutrition, 2026)
BackgroundSustainable sports nutrition is increasingly recognized as a means of enhancing the athlete’s performance while reducing negative environmental impacts, however, empirical data in the context of adolescent athletes is limited.ObjectivesThis study examined sport nutrition knowledge, environmental awareness, and sustainable dietary behaviors among adolescent athletes, and their associated with motivation and sports participation.MethodsA mixed-methods design was used to examine sustainable nutrition behaviors and their motivational, contextual, and social determinants. A total of 312 athletes were invited to participate, and 120 completed a structured survey (response rate: 38%). Measures included a modified Sport Nutrition Knowledge Questionnaire, a validated environmental awareness subscale (α > 0.78), and a composite Sustainable Practice Score (SPS; α = 0.81).Results and discussionQuantitative analyses showed that 78% of the participants reported moderate awareness of the environmental impact of food choices, and 62% had adopted at least one sustainable dietary practice. SPS was positively correlated with sports nutrition knowledge (r = 0.39, p < 0.001) and environmental awareness (r = 0.46, p < 0.001). Regression analyses indicated that sustainable nutrition practices significantly predicted motivation (β = 0.32, p < 0.01) and participation frequency (β = 0.29, p < 0.01), with environmental awareness moderating both relationships. Qualitative findings highlighted perceived physiological benefits, social influences, and structural barriers as a key theme influencing adoption.ConclusionIn general, adolescent athletes demonstrated developing and context-dependent sustainable dietary behaviors shaped by nutrition knowledge, environmental awareness, and socio-cultural influences. Enhancing sustainability-oriented educational interventions within youth sport settings may support both performance-related outcomes and the development of environmental responsibility.